Post-Genocide, Post-Apartheid: The Shifting Landscapes of African Philosophy, 1994–2019 - Alena Rettová (Modern Africa, 2021)
This article traces the developments of African philosophy since 1994, a year marked by two events that profoundly impacted Africa: the fall of apartheid and the Rwandan genocide. The article projects a fundamental tension into the history of recent African philosophy: between optimism and idealism, showing in the development of normative concepts and a new philosophical vocabulary for Africa – a “conceptual mandelanization” (Edet 2015: 218), on the one hand, and a critical realism ensuing from the experience of African “simple, that is, flawed, humanity” (Nganang: 2007: 30), on the other. The article identifies prominent trends in African philosophy since 1994, including Ubuntu, the Calabar School of Philosophy, Afrikology, the Ateliers de la pensée, Francophone histories of African philosophy, and Lusophone political and cultural philosophy.